The invisible presence of women athletes in the Spanish sports press. Analysis of the front pages of "Marca", "As", "Mundo Deportivo" and "Sport" (2010-2015) - Gómez-Colell, Eva; Medina-Bravo, Pilar; Ramon, Xavier (Estudios sobre el Mensaje Periodístico, 2017)
The reality of women continues to be explained by the media from an androcentric perspective, despite a greater female presence in the public sphere. In the context of sports journalism, the media coverage of athletes is modest, even null. Qualitatively, information about women and their activity repeatedly refers to gender stereotypes. This is because both sport itself and sports journalism have been constructed as a predominantly male territory, where gender inequalities and gender bias have been legitimized. This research analyzes the front pages of the four most widely read sports journals in Spain (Marca, As, Mundo Deportivo and Sport) over a period of five years (2010-2015), the results of which reaffirm that "sport continues to exist, for and on men" (Cooky et al., 2013: 205).